Advances in Databases and Information Systems: 17th East European Conference, ADBIS 2013, Genoa, Italy, September 1-4, 2013. Proceedings - Catania, Barbara; Guerrini, Giovanna; Pokorný, Jaroslav (Lecture notes in computer science, 2013)
This book constitutes the thoroughly refereed proceedings of the 17th East-European Conference on Advances in Databases and Information Systems, ADBIS 2013, held in Genoa, Italy, in September 2013. The 26 revised full papers presented together with three invited papers were carefully selected and reviewed from 92 submissions. The papers are organized in topical sections on ontologies; indexing; data mining; OLAP; XML data processing; querying; similarity search; GPU; querying in parallel architectures; performance evaluation; distributed architectures.
Literaturangaben
Keywords: Konferenzschrift -- 2013 -- Genua; Konferenzschrift; Anwendungssystem; Information Retrieval; Data Mining; Abfrage; Datenbanksystem